Raúl Orlando Pérez, a Story of Excepcionality - Pérez, Pablo A. (2023)
This paper exposes the figure of a man born in Argentina who, through his works, has achieved international significance in the world of artistic expressions, especially in field of music and instrument building, as well as painting. The scope of his legacy is also postulated from the qualitative patrimonial approach, in all probability not yet fully valued.